Interactions between coagulation and complement—their role in inflammation - Oikonomopoulou, Katerina (2011)
The parallel expression of activation products of the coagulation, fibrinolysis, and complement systems has long been observed in both clinical and experimental settings. Several interconnections between the individual components of these cascades have also been described, and the list of shared regulators is expanding. The coexistence and interplay of hemostatic and inflammatory mediators in the same microenvironment typically ensures a successful host immune defense in compromised barrier settings. However, dysregulation of the cascade activities or functions of inhibitors in one or both systems can result in clinical manifestations of disease, such as sepsis, systemic lupus erythematosus, or ischemia–reperfusion injury, with critical thrombotic and/or inflammatory complications. An appreciation of the precise relationship between complement activation and thrombosis may facilitate the development of novel therapeutics, as well as improve the clinical management of patients with thrombotic conditions that are characterized by complement-associated inflammatory responses.